Biphasic regulation of CFTR expression by ENaC in epithelial cells: The involvement of Ca2+-modulated cAMP production - Wuchu, Fulei; Ma, Xiyang; Que, Yanting; Chen, Junjiang; Ruan, Ye Chun (Frontiers in Cell and Developmental Biology, 2022)
The regulatory interaction between two typical epithelial ion channels, cystic fibrosis transmembrane conductance regulator (CFTR) and the epithelial sodium channel (ENaC), for epithelial homeostasis has been noted, although the underlying mechanisms remain unclear. Here, we report that in a human endometrial epithelial cell line (ISK), shRNA-based stable knockdown of ENaC produced a biphasic effect: a low (~23%) degree of ENaC knockdown resulted in significant increases in CFTR mRNA and protein levels, CFTR-mediated Cl- transport activity as well as intracellular cAMP concentration, while a higher degree (~50%) of ENaC knockdown did not further increase but restored CFTR expression and cAMP levels. The basal intracellular Ca2+ level of ISK cells was lowered by ENaC knockdown or inhibition in a degree-dependent manner. BAPTA-AM, an intracellular Ca2+ chelator that lowers free Ca2+ concentration, elevated cAMP level and CFTR mRNA expression at a low (5µM) but not a high (50 µM) dose, mimicking the biphasic effect of ENaC knockdown. Moreover, KH-7, a selective inhibitor of soluble adenylyl cyclase (sAC), abolished the CFTR upregulation induced by low-degree ENaC knockdown or Ca2+ chelation, suggesting the involvement of sAC-driven cAMP production in the positive regulation. A luciferase reporter to indicate CFTR transcription revealed that all tested degrees of ENaC knockdown/inhibition stimulated CFTR transcription in ISK cells, suggesting that the negative regulation on CFTR expression by the high-degree ENaC deficiency might occur at post-transcription stages. Additionally, similar biphasic effect of ENaC knockdown on CFTR expression was observed in a human bronchial epithelial cell line. Taken together, these results have revealed a previously unidentified biphasic regulatory role of ENaC in tuning CFTR expression involving Ca2+-modulated cAMP production, which may provide an efficient mechanism for dynamics and plasticity of the epithelial tissues in various physiological or pathological contexts.